Surface Chemistry of tert‐Butylphosphine (TBP) on Si(001) in the Nucleation Phase of Thin‐Film Growth. Issue 42 (30th August 2016) - Stegmüller, Andreas; Werner, Katharina; Reutzel, Marcel; Beyer, Andreas; Rosenow, Phil; Höfer, Ulrich; Stolz, Wolfgang; Volz, Kerstin; Dürr, Michael; Tonner, Ralf
Abstract: We combine density functional theory calculations and scanning tunneling microscopy investigations to identify the relevant chemical species and reactions in the nucleation phase of chemical vapor deposition. tert ‐Butylphosphine (TBP) was deposited on a silicon substrate under conditions typical for surface functionalization and growth of semiconductor materials. On the activated hydrogen‐covered surface H/Si(001) it forms a strong covalent P−Si bond without loss of the tert ‐butyl group. Calculations show that site preference for multiple adsorption of TBP is influenced by steric repulsion of the adsorbate's bulky substituent. STM imaging furthermore revealed an anisotropic distribution of TBP with a preference for adsorption perpendicular to the surface dimer rows. The adsorption patterns found can be understood by a mechanism invoking stabilization of surface hydrogen vacancies through electron donation by an adsorbate. The now improved understanding of nucleation in thin‐film growth may help to optimize molecular precursors and experimental conditions and will ultimately lead to higher quality materials. Abstract : Crystal growth : Surface chemistry of tert ‐butyl phosphine on a H/Si(001) surface under thin‐film deposition conditions has been studied by DFT calculations and STM measurements of samples grown by MOVPE by a newly developed transfer method. Anisotropic chain formation at sub‐monolayer coverage was found (see figure). The nature of surface species and an adsorption mechanism is revealed, and the necessity of surface hydrogen vacancies for the adsorbate distribution observed.